Improving the Ability to Write Fantasy Story Texts with the Discovery Learning Model for Class VII C . Students SMP Negeri 4 Kendari Kendari City - arifin arifin (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
This study conducted under Classroom Action Research design aims at improving the ability in writing fantasy stories of VII C students in SMP Negeri 4 Kendari by applying the Discovery Learning model. This research consists of 32 students of VII C enrolled in the first semester of 2019/2020. The subject includes 13 male students and 19 female students. Each cycle is completed within two cycles and covers four stages: planning, action, observation, and reflection. Data from this study were obtained both by test for measuring students' skills in writing and non-test in the form of an observation sheet for assessing the learning activities of the teacher and the students. The data were analyzed by using quantitative and qualitative descriptive. The study's findings revealed an improvement in the students' ability to write fantasy stories for the students of VII C in SMP Negeri 4 Kendari. In cycle, I the percentage of progress of students' mean score was 81.25% which became 100% in cycle II. The number implied that there were no more students in the class categorized as failing on writing fantasy stories in cycle II. Therefore, this research ends in the second cycle, concluding that the discovery learning model has been proved to improve students' skills in writing fantasy stories of the VII C students in SMP Negeri 4 Kendari.